Kontroversi Pemberian Alat Kontrasepsi dalam PP 28/2024 terhadap Prinsip Pendidikan dan UU Perkawinan - Indy Azzahra Putri (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study discusses the conflict between Government Regulation Number 28 of 2024 concerning the provision of contraceptives for students with the principles contained in the Child Marriage Law and the National Education System in Indonesia. Although this policy aims to prevent early pregnancy and transmission of sexually transmitted diseases, the provision of contraceptives for students raises concerns because it is considered to legitimize sexual activity among adolescents. This is compared to child protection efforts as stated in the Marriage Law which stipulates the minimum age of marriage and moral values ​​in education. This study uses a normative legal approach to analyze the implications of the policy on children's rights, the education system, and social and cultural values. The results of the study indicate that this policy has the potential to violate the goals of national education and child protection. Therefore, a more balanced policy revision is needed, by integrating comprehensive sex education based on moral values, in order to protect children's rights while providing appropriate education for adolescents.